Tradisi Unduh Patirtan di Desa Kembangbelor, Kecamatan Pacet, Kabupaten Mojokerto (Tintingan Folklor) - Savira Ratu Kezia Devani Anjaliva (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
Tradition Unduh Patirtan is one of the traditions in Kembangbelor village, Pacet district, Mojokerto district. This tradition still exists and is still preserved. This tradition is interesting to follow. This research will be search of Tradisi Unduh Patirtan behavior. This research uses descriptive research qualitative methods. The data is obtained through direct observations, interviews, documentation, and transcripts. The series of events carried out in Tradisi Unduh Patirtan is Khataman al-Kuran, reboisation, arrangement of pambuka and arrangement papundhen, arrangements of the story of wayang beber, undhuh patirtan, umbul donga lan spell, napak tilas tirta, kirab matirta, bantengan, Kirab ancak, madhang sega pancawarna. Ubarampe Tradisi Unduh Patirtan This is siwur, gentong, kendi, leaves of kelor, sega pancawarna, snake of market, pala pendhem, dupa, kethuk, and gong. Tradisi Unduh Patirtan functions are the projection system, cultural validation, educational means, overseeing the rules of society, there are also other functions such as economic functions, gotong royong functions and religious functions. There's been a change in the behavior and ubarampe of this Tradisi Unduh Patirtan. In order not to suffer change or loss of culture must be carried out for conservation, conservation of this Tradisi Unduh Patirtan through government, society, education, and social media.